POTENSI ESTIMASI KARBON TERSIMPAN PADA VEGETASI MANGROVE DI WILAYAH PESISIR MUARA GEMBONG KABUPATEN BEKASI - Ditha Rachmawati; Isdradjad Setyobudiandi; Endang Hilmi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2014)
Mangrove Muara Gembong can be considered as buffering system of high CO2 produced by industries in Bekasi. This study aims to determine the carbon stored in standing mangrove’s Muara Gembong. The research was conducted on March 2014 in the coastal area of Muara Gembong, Bekasi Regency West Java. The method used in this study is a survey method with sampling purposive sampling technique. The results showed that the degree of dominance of mangrove species in Muara Gembong at station I, II, III and IV were Rhizophora mucronata, Sonneratia alba, S. caseolaris, R. mucronata. Potential carbon stored of mangrove stands in Muara Gembong is 55,35 tons ha, with the highest carbon stored in mangrove species Rhizophora mucronata is 17,60 tons/ha. Based on the potential of biomass and carbon being produced, showed that the ability of mangrove ecosystem to absorbing carbon in Muara Gembong is not too high.Keywords : Carbon sink, conservation, global warming, mangrove, Muara Gembong